Stationary cycling exercise for knee osteoarthritis: A systematic review and meta-analysis. (April 2021) - Luan, Lijiang; Bousie, Jaquelin; Pranata, Adrian; Adams, Roger; Han, Jia
Objective: To evaluate effects of stationary cycling exercise on pain, function and stiffness in individuals with knee osteoarthritis. Data sources: Systematic search conducted in seven databases (PubMed, Embase, Cochrane Library, Web of Science, EBSCO, PEDro, and CNKI) from inception to September 2020. Review methods: Included studies were randomized-controlled trials involving stationary cycling exercise conducted on individuals with knee osteoarthritis. End-trial weighted mean difference (WMD) and 95% confidence interval (CI) were analyzed, and random-effects models were used. Methodological quality and risk bias were assessed by using the Physiotherapy Evidence Database scale and Cochrane Collaboration tool, respectively. Results: Eleven studies with 724 participants were found, of which the final meta-analysis was performed with eight. Compared to a control (no exercise), stationary cycling exercise resulted in reduced pain (WMD 12.86, 95% CI 6.90–18.81) and improved sport performance (WMD 8.06, 95% CI 0.92–15.20); although most of the meta-analysis results were statistically significant, improvements in stiffness (WMD 11.47, 95% CI 4.69–18.25), function (WMD 8.28, 95% CI 2.44–14.11), symptoms (WMD 4.15, 95% CI −1.87 to 10.18), daily living (WMD 6.43, 95% CI 3.19 to 9.66) and quality of life (WMD 0.99, 95% CI −4.27 to 6.25) for individuals with knee osteoarthritis were not greater than the minimal clinically important difference values for each of these outcome measures. Conclusions: Stationary cycling exercise relieves pain and improves sport function in individuals with knee osteoarthritis, but may not be as clinically effective for improving stiffness, daily activity, and quality of life.